ANALISIS STRUKTUR PEREKONOMIAN BERDASARKAN PENDEKATAN SHIFT – SHARE DALAM PENGEMBANGAN AGROWISATA DI KABUPATEN CIREBON - Nur Syamsiyah; Ganjar Kurnia (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to analyze the economic structure based on the Shift-share approach in developing agro-tourism in Cirebon Regency with 4 components namely National Growth, Industrial Mix or Proportional Growth, Competitive Advantage / Regional Growth (PPW), Total Growth based on PDRB Year 2011 - Year 2014. The research method using quantitative descriptive analysis, Shift Share Analysis is used to determine the process of economic growth of a region. The results showed that the development of agro-tourism through basic commodities in Cirebon Regency is very useful. Growth The area of each sector is 0.19, the agricultural sector including the sector with the second highest growth value after the manufacturing sector. The proportional growth of the agricultural sector falls into 5 sectors that have slow growth rates. So through the development of agro-tourism is expected to increase the growth of the agricultural sector, and the agricultural sector in Cirebon Regency increasingly lost competitiveness. The resulting product is difficult to compete with the diverse products in the market. The sector with the highest increase of competitiveness is the service sector of the company while the losing sector of competitiveness is the manufacturing sector. Thus, government support through policies, taxes, subsidies, institutions and market access can increase economic growth in Cirebon Regency.